1976
DOI: 10.1136/hrt.38.11.1204
|View full text |Cite
|
Sign up to set email alerts
|

Antilipolytic therapy in angina pectoris. Reduction of exercise-induced ST segment depression.

Abstract: A double-blind cross-over study was performed on 12 men sith stable angina pectoris in order to determine the effect of antilipolytic treatment on exercise tolerance and exercise-induced electrocardiographic changes. The men were exercised to the onset of anginal pain using a reproducible and standardized ergometric load. A nicotinic acid analogue was used to reduce plasma free fatty acids and free glycerol before and during exercise testing and to eliminate their post-exercise rise. This was associated with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1979
1979
1991
1991

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Some reports indicate that infusion of neutral lipid and heparin in dogs with myocardial ischemia exacerbates arrhythmia (Kurien et al, 1969(Kurien et al, , 1971), but results have been inconsistent (Opie et al, 1971). In patients, antipolytic agents decrease ST alterations induced by exercise or ischemia (Luxton et al, 1976;Russell and Oliver, 1978b) with a concomitant reduction of plasma FFA (Russell and Oliver, 1978b). Antiarrhythmic effects are particularly marked when the induced fall in plasma free fatty acids is rapid (Rowe et al, 1975).…”
Section: Electrophysiological Effects Of Fatty Acidsmentioning
confidence: 99%
“…Some reports indicate that infusion of neutral lipid and heparin in dogs with myocardial ischemia exacerbates arrhythmia (Kurien et al, 1969(Kurien et al, , 1971), but results have been inconsistent (Opie et al, 1971). In patients, antipolytic agents decrease ST alterations induced by exercise or ischemia (Luxton et al, 1976;Russell and Oliver, 1978b) with a concomitant reduction of plasma FFA (Russell and Oliver, 1978b). Antiarrhythmic effects are particularly marked when the induced fall in plasma free fatty acids is rapid (Rowe et al, 1975).…”
Section: Electrophysiological Effects Of Fatty Acidsmentioning
confidence: 99%
“…According to some investigators (15) the toxic effects of elevated [FFA] may not occur until the plasma level exceeds the level needed to saturate the binding sites on blood albumin. This is thought to correspond with an [FFA] of about 1800 /jmol/liter (16) when the [FFA]/albumin molar ratio exceeds 3. At this concentration there is thought to be an increase in the level of unassociated fatty acids in the blood and interstitial fluid (15).…”
Section: Discussionmentioning
confidence: 96%
“…Recently it has been shown that cultured bovine aortic endothelial cells accumulate fatty acids from the perfusing medium when [FFA] exceeds only 500 //mol/ liter (11). Furthermore, the reduction of [FFA] from 700 /imol/liter to 350 jtmol/ liter has been found to reduce ST-segment depression in coronary patients undergoing stress tests (16). ST-segment depression measured from an ECG is an index of myocardial oxygenation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antilipolytic treatment has recently been shown to reduce the ischaemic injury in these patients [I 1, 301 and to reduce the exercise-induced ST-segment depression in patients with angina pectoris [15]. In experimental studies elevated plasma FFA concentrations enhance myocar-0036-551 3/79/ 1000-0559$02.00 0 1979 Medisinsk Fysiologisk Forenings Forlag dial oxygen consumption [3, 171, suggesting that the deleterious effect of FFA during myocardial ischaemia may reflect an increased oxygen requirement in ischaemic tissue.…”
mentioning
confidence: 99%